2021
DOI: 10.1212/wnl.0000000000011537
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dilated Perivascular Spaces With Cognitive Decline and Incident Dementia

Abstract: Objective:To determine if severe perivascular space (PVS) dilation is associated with longitudinal cognitive decline and incident dementia over four and eight years respectively, we analyzed data from a prospective cohort study.Methods:414 community dwelling older adults aged 72-92 were assessed at baseline and biennially for up to eight years, with cognitive assessments, consensus dementia diagnoses and 3T MRI imaging. The numbers of PVS in two representative slices in the basal ganglia (BG) and centrum semio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 37 publications
2
68
0
Order By: Relevance
“…Clinical research data have proved that ePVS is a risk factor for cognitive impairment and dementia. The ePVS is an important risk factor for cognitive decline in Parkinson's disease and Alzheimer's disease, as well as vascular cognitive impairment and vascular dementia ( 21 , 41 43 ). However, we found no significant difference between MMSE and BG-ePVS score and CSO-ePVS score.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical research data have proved that ePVS is a risk factor for cognitive impairment and dementia. The ePVS is an important risk factor for cognitive decline in Parkinson's disease and Alzheimer's disease, as well as vascular cognitive impairment and vascular dementia ( 21 , 41 43 ). However, we found no significant difference between MMSE and BG-ePVS score and CSO-ePVS score.…”
Section: Discussionmentioning
confidence: 99%
“…Advancing age and increasing burdens of CMBs and WMHs may obliterate the PVSE effect on cognition. Previous studies on the PVSE association with cognitive domain-specific analyses demonstrated discrepant findings: no PVSEs in any brain region associated with any cognitive domains, BG PVSEs associated with worse visuomotor speed, PVSEs in the hippocampus linked to better memory, and total PVSEs related to lower global cognition, non-verbal reasoning, and visuoexecutive function (18,(67)(68)(69)(70)(71)(72). These inconsistent results imply insufficient evidence connecting either total or regional PVSEs with declines in specific cognitive domains.…”
Section: Discussionmentioning
confidence: 92%
“…The most often used scales are the medial temporal atrophy scale (MTA), the global cortical atrophy scale (GCA), and white matter hyperintensities [42,50,51]. The consensus regarding PVS is that they play a role in fluid transport, in exchange between cerebrospinal fluid and interstitial fluid, and in the removal of waste products from the brain (including Aβ) [52] There are research articles that indicate the connection of PVS dilation with small vessel disease and stroke [53,54]; cognitive decline and dementia [15,20].…”
Section: Discussionmentioning
confidence: 99%